Analysis Of Work Discipline, Job Satisfaction, And Work Environment On Employee Performance At The Local Police And Fire Department Of Langkat Regency - Fahri Dwi Wardana; Abdi Setiawan; Kholilul Kholik (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study is to analyze the effects of work discipline, job satisfaction, and work environment on employee performance at the Regional Civil Service Police Unit and Fire and Rescue Department of Langkat Regency. This study applies a quantitative approach using a survey method by distributing questionnaires to 72 respondents selected through proportionate stratified random sampling. The data were analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The results indicate that work discipline, job satisfaction, and work environment individually have a positive and significant effect on employee performance. Simultaneous testing also confirms that the three independent variables collectively have a significant effect on employee performance. The coefficient of determination shows that a substantial proportion of the variation in employee performance is explained by the proposed model. These findings provide empirical implications for human resource management in public sector organizations, particularly in improving employee performance through strengthened work discipline, enhanced job satisfaction, and improved work environment.